Cochlear Implant Magnet Dislocation Caused by 1.5T MRI: Case Series Study - Koda, Kento; Kashio, Akinori; Uranaka, Tsukasa; Hoshi, Yujiro; Takenouchi, Shigeo; Matsumoto, Yu; Iwasaki, Shinichi; Yamasoba, Tatsuya (Archives of Clinical and Medical Case Reports, 2020)
Magnet dislocation (MD) is a serious concern for cochlear implant users. The frequency of magnetic resonance imaging (MRI) examination is much higher in Japan than in other countries, which may be a major problem for cochlear implant users. Here, we report two cases in which 1.5T MRI caused severe pain and MD of the cochlear implant. Both patients received cochlear implants manufactured by Cochlear Ltd., which are compatible with 1.5T MRI. Both patients experienced MD; in one case, manual fixation was attempted. Radiography revealed that the magnet seemed to be successfully fixed; however, ultrasonic echo indicated dislocation, and the magnet was finally fixed surgically. In the other case, the cochlear implant was surgically replaced because the original implant had a cracked silicon bed. Ultrasonic echo was a useful tool for visualizing the precise location of the magnet. Even when a magnet is successfully repositioned by manual fixation, the possibility that the silicon bed is also seriously damaged remains. Surgical fixation of the magnet is recommended to investigate whether or not the silicon bed is damaged, especially for patients who need to undergo repeat MRI examinations for follow-up. <gdiv></gdiv>